Analyzing the impact of coastal land use on seawater quality in the Bohai Rim of China - Ruiqian Li; Yuhan Zhao; Xun Zeng; Wanlei Mao (Marine Development)
Abstract Against the backdrop of rapid urbanization and industrialization, land use in coastal areas substantially impacts the marine environment. However, comprehensive analyses of the relationship between land use and marine environments are lacking, especially in the context of long-term data and within the framework of land–sea integrated governance. By establishing a theoretical framework, this research utilizes remote sensing data to invert seawater quality indicators and employs a panel data regression model to assess the long-term effects of coastal land use changes on seawater quality in the Bohai Rim from 2001 to 2020. The study reveals a U-shaped trend in seawater quality, with an initial decline followed by an improvement and significant regional variations. There is a notable shift in land use structure, with increases in grassland, construction land, and forest land areas at the expense of croplands. The expansion of construction land has a more pronounced negative impact on seawater quality compared with other land use types, particularly during the early stages of regional integration policies. Increasing ecological land can improve seawater quality, especially when it bolsters ecological functions and the marine environment’s carrying capacity. This study highlights the need for strategic marine environmental protection within the context of regional spatial governance. It advocates for policies that optimize land use, enhance ecological frameworks, and foster coordination among various stakeholders. This research provides key insights for advancing land–sea integrated governance, which is essential for sustainable marine conservation in coastal regions.